Abnormal perilesional BOLD signal is not correlated with stroke patients’ behavior - de Haan, Bianca; Rorden, Chris; Karnath, Hans-Otto (Frontiers in Human Neuroscience, 2013)
Several fMRI studies of acute stroke have reported that patients with behavioral deficits show abnormal signal in intact regions of the damaged hemisphere close to the lesion border relative to homologous regions of the patient’s intact hemisphere (causing an interhemispheric imbalance) as well as analogous regions in healthy controls. These effects have been interpreted as demonstrating a causal relationship between the abnormal fMRI signal and the pathological behavior. Here we explore an alternative explanation: perhaps the abnormal BOLD fMRI signal is merely a function of distance from the acute lesion. To investigate this hypothesis, we examined three patients with an acute right hemisphere cortical stroke who did not show any overt behavioral deficits, as well as nine healthy elderly controls. We acquired fMRI data while the participants performed a simple visual orientation judgment task. In patients, we observed an abnormal interhemispheric balance consisting of lower levels of percent signal change in perilesional areas of the damaged hemisphere relative to homologous areas in neurologically healthy controls. This suggests that the physiological changes and corresponding interhemispheric imbalance detected by fMRI BOLD in acute stroke observed close to the lesion border may not necessarily reflect changes in the neural function, nor necessarily influence the individuals’ (e.g. attentional) behavior.